QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

13C solid-state nuclear magnetic resonance and Fourier transform infrared studies of the thermal decomposition of cork. - Pascoal Neto, C.; Rocha, J.; Gil, A.; Cordeiro, N.; Esculcas, a P.; Rocha, S.; Delgadillo, I.; de Jesus, J. D.; Correia, a J. (Solid state nuclear magnetic resonance, 1995)
The thermal decomposition of cork has been studied by Fourier transform infrared (FTIR) spectroscopy and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy with cross-polarization and magic-angle spinning (CP-MAS), high-power 1H decoupling (HPDEC) and cross-polarization depolarization-polarization (CPDP). Waxes and other soluble components of cork begin to decompose at ca. 150 degrees C. This is accompanied by partial decomposition of suberin, probably initiated at the points of attachment to the cell wall. The carbohydrates begin to decompose at ca. 200 degrees C. The decomposition of lignin begins at 250-300 degrees C, while suberin undergoes further degradation. Significant amounts of coke are formed in the process. At 400 degrees C cork has been transformed into coke with traces of partially decomposed suberin. The thermal decomposition of cork is dependent on the calcination time, particularly in the 200-350 degrees C range.
The following values have no corresponding Zotero field: accession-num: 7773647
Keywords: Fourier Transform Infrared (citation); Hot Temperature; Lignin; Lignin: chemistry; Lipids; Magnetic Resonance Spectroscopy; Membrane Lipids; Membrane Lipids: chemistry; Polysaccharides; Polysaccharides: chemistry; Spectroscopy